A Systematic Literature Review on Construction Management Productivity Enhancement by utilizing Business Information Modeling - Saja, Abd Alrazaq Khamees; Sawsan, Rasheed Mohammed (Engineering, Technology & Applied Science Research, 2024)
The systematic review of Business Information Modeling (BIM) plays a crucial role in understanding its significance and impact. This review allows for a comprehensive examination of the existing literature, highlighting the benefits, challenges, and success factors associated with BIM. There is a scarcity of studies dealing with this subject, and so a question about the most important advantages that will be obtained by the construction industry, especially the construction companies, as a result of the BIM application arises. Relevant previous studies were reviewed and their quality was evaluated using a systematic methodology. The current study was characterized by the use of the SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis technique. As far as is known, the current study is the first of its kind in the field of Iraqi project management. The results suggest that the BIM benefits include firm’s growth, organizational performance, enhanced market value, employee motivation, and service quality.